Integrating Technology into Teaching to Foster Student Engagement and Interaction - Wastira, Jarudin; Bronto Waluyo, Edy Tekad; Fajarianto, Otto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Rapid advances in educational technology have renewed calls for evidence-based models that translate digital tools into genuine gains in classroom engagement and peer interaction. This study investigates the impact of a purpose-built technology-integration framework in junior high school science lessons, combining a learning management system, live polling, and collaborative white-boarding. Employing a quasi-experimental, mixed-methods design, 102 students from two comparable schools were assigned to either an intervention class (n = 52) or a business-as-usual control (n = 50) for one semester. Pre- and post-test data were gathered with a validated Engagement in Learning Scale and an observation rubric tracking verbal and non-verbal interaction events. At the same time, click-stream analytics and semi-structured interviews triangulated the quantitative findings. ANCOVA results indicated a significant treatment effect on overall engagement (F(1, 98) = 15.27, p < .001, Hedges g = 0.63) and student-initiated interaction frequency (ΔM = 14.6 events per class, p = .002). Thematic analysis of 1,274 coded reflections revealed that instant feedback, visual progress cues, and low-stakes collaborative tasks were perceived as the chief motivators of participation. Collectively, the data suggest that strategically layered technologies can shift classroom dynamics from teacher-centered recitation toward student-driven discourse without extending instructional time. Limitations include single-subject focus and reliance on self-report for some measures. Future work should examine long-term retention effects and scalability across diverse curricular areas.